Measurement of Sustainable Development with Electrification of Households in Indonesia - Permana, Meiki; Rochaida, Eny; Mire, Muhammad Saleh; Suharto, Rahcmad Budi (International Journal of Energy Economics and Policy, 2021)
This study offers Sustainable Development Measurement using three variables, namely; The Human Development Index (HDI) represents Sustainable Social Economic Development, and the Environmental Quality (EQ) represents Environmental Sustainability, while the Exogenous Variable is Household Electrification (EoH). With Analysis Using Structural Equation Modeling, the results showed; EoH positively and significantly correlated to HDI. EoH is negatively correlated and significant to EQ. HDI significantly negatively correlated with EQ. Electrification of Households causes the occurrence of Sustainable Social Economic Development, and vice versa, the electrification of households causes the occurrence of environmental sustainability, and the relationship of sustainable Social Economic Development causes the occurrence of environmental sustainability. Research Novelty is the Role of Moderation from EoH to the relationship between HDI and EQ so that provinces with low Household Electrification with Provinces with high Household Electrification will differ in environmental damage due to Sustainable Social Economic Development. Reference for Policy Makers to replace fossil fuel power plants that supply the electricity in households with environmentally friendly power plants. Keywords: Sustainable Development, Household Electrification, Structural Equation Modeling JEL Classifications: Q01, L94, C38 DOI: https://doi.org/10.32479/ijeep.10937